Manifestly uncertain destiny: the debate over American expansionism, 1803-1848 - McDonough, Matthew Davitian (Kansas State University, 2011)
Americans during the first half of the nineteenth-century were obsessed with expansion. God had bestowed upon them an innate superiority in nearly all things. American settlers were culturally, economically, racially and politically superior to all others. But how accurate are such statements? Did a majority of Americans support such declarations? The purpose of this dissertation is to examine how Americans wrote and read about expansion. Doing so reveals that for every citizen extolling the unique greatness of Americans, one questioned such an assumption. For every American insisting that the nation must expand to the Pacific coast to be successful there was one who disdained expansion and sought to industrialize what territory the nation already possessed. Americans during the first half of the nineteenth century were of many minds about expansion. The destiny of the United States was anything but manifest. Using a wealth of nineteenth century newspapers this dissertation demonstrates that the concept of Manifest Destiny was far less popular than previously imagined. Newspapers were the primary source of information and their contents endlessly debated. Editors from around the country expressed their own views and eagerly published pertinent letters to the editor that further detailed how Americans perceived expansion. While many people have often read John O’Sullivan’s rousing words he was not necessarily indicative of American sentiment. For every article espousing the importance of acquiring Florida to deny it to the British there was one deriding the notion because they felt Florida to be nothing but a worthless swamp filled with hostile Indians. American justification and opposition to territorial expansion followed no grand strategy. Instead, its most fascinating characteristic was its dynamic nature. In the Southwest expansionist proponents argued that annexation would liberate the land from Papist masters, while opponents questioned the morality of such a conquest. Encouraging or discouraging territorial expansion could take on innumerable variations and it is this flexible rhetoric that the dissertation focuses upon. The debate that raged in the public forum over expansion was both heated and fascinating. The voices of both pro and anti-expansionists were crucial to the development of antebellum America.
Keywords: Manifest destiny; Newspapers; Nineteenth century; Expansion; Public opinion; Journalism; American History (0337); History (0578); Journalism (0391)